Retribusi Pelayanan Publik dan Kinerja Pendapatan Asli Daerah: Bukti Empiris di Kabupaten Sukoharjo - Destantya Mayang Karisma; Yenni Khristiana; Anton Respati Pamungkas (ProBank, 2026)
This study aims to examine the effect of market service retribution, waste/cleanliness service retribution, and special parking service retribution on the Regional Original Revenue (PAD) of Sukoharjo Regency during the 2021–2024 period. This research employs a quantitative approach using secondary data obtained from the Regional Financial Management Agency of Sukoharjo Regency. The data were analyzed using multiple linear regression analysis. The results show that market service retribution and waste/cleanliness service retribution have a positive and significant effect on PAD, while special parking service retribution does not have a significant effect. Simultaneously, all retribution variables significantly influence PAD. These findings imply that improving the effectiveness of regional retribution management can enhance local revenue performance.